Dynamic reorganization of vortex matter into partially disordered lattices - Marziali Bermudez, Mariano (2015)
We report structural evidence of dynamic reorganization in vortex matter in clean NbSe2 by joint small-angle neutron scattering and ac susceptibility measurements. The application of oscillatory forces in a transitional region near the order-disorder transition results in robust bulk vortex lattice configurations with an intermediate degree of disorder. These dynamically originated configurations correlate with intermediate pinning responses previously observed, resolving a long-standing debate regarding the origin of such responses.